El registro de explotaciones y sus posibilidades en la investigación geográfica - Alberdi Collantes, Juan Cruz (Geographicalia, 2016)
In this paper we study the possibilities to the farm geography investigation of a new information way, the farm register. This source picks up exploitation main information about the family work, farm activity and production, propriety of the land cover, uses and their relations whit the propriety register and its cartography. In the paper we analyse two practical examples, the typology of sheep exploitation and the use of the land cover in the Basque Country farm exploitation. First, we see two different ways for all production sector: one conducting to the specialisation and increasing productions capacity; and other, more extended, conducting to the abandon of all farm activity. In the second example, we see that the farm use depend of a little farmers number, the cattle who has take the decision of continue with the farm activity.